Assessment of environmental enrichment for different primate species under low budget: A case study. Issue 2 (3rd April 2018) - Costa, R.; Sousa, C.; Llorente, M.
ABSTRACT: The 2011 European Union Zoo Inquiry presented evidence that most zoos fail to achieve adequate levels of nonhuman animal welfare. Appropriate environmental enrichment (EE) can play a role in the promotion of welfare. However, financial and staff constraints frequently make it challenging to implement EE on a daily basis. The aim of this study was to test how individuals of three different nonhuman primate species at the Maia Zoo in Portugal (white-handed gibbons, Hylobates lar ; Mona monkeys, Cercopithecus mona ; and brown lemurs, Eulemur fulvus ) reacted to EE devices. Another aim was to investigate whether simple, inexpensive devices can have positive outcomes for animal welfare. The results showed that all individuals reacted to the EE intervention, but individual responses to the EE devices differed. EE devices had consistently positive effects for all three species as demonstrated by an increase in the expression of natural behaviors and a general decrease in abnormal behaviors (46% compared with baseline). This study demonstrates that it is important to simultaneously test multiple individuals from different species in different situations to evaluate the effectiveness of EE.